RANCANG BANGUN APLIKASI MEDIA PEMBELAJARAN MENGENAL NAMA HEWAN DALAM DUA BAHASA BERBASIS ANDROID MENGGUNAKAN THUNKABLE - Gunadi, Goldie (ISTEK WIDURI, 2020)
With the rapid development of Android-based smartphone technology devices, many learning media applications for multimedia-based children have been developed, the aim of which is to increase children's interest and motivation to learn in order to better receive the learning material provided. In this study, an Android-based animal recognition application design was carried out using two languages namely Indonesian and English. The design process is done using UML modeling, while the process of making an application is done using a tool that is Thunkable. With Thunkable the process of making applications becomes easier, faster and efficient. To ensure that every functional application runs properly in accordance with expectations, Black-Box testing is performed. The results of this study are an Android application that uses a variety of multimedia resources such as images, audio (sound) and video, as well as having an attractive and easy to use interface so that it can help early childhood children learn the material presented in this application.